Campur Kode dalam Lagu Berbahasa Bali Group Kiss Band yang Berjudul Jauh Panggang dari Api - Niva Shanti, Ni Wayan Ari (Dharma Sastra : Jurnal Penelitian Bahasa dan Sastra Daerah, 2025)
This research is entitled "Mixing Codes in Balinese Language Songs by the Kiss Band Group entitled Jauh Panggang Dari Api", Code mixing refers to the use of a dominant or primary language that functions independently in communication. Other languages that appear within the speech act only serve as fragments and do not possess autonomous roles as codes. This phenomenon occurs when a speaker primarily employs one language while incorporating certain linguistic elements from another to enrich or emphasize the message. Balinese songwriters in today's era who create songs  is by mixing one language with another. One of them is the singer of Bali Kiss Band, almost all songs owned by Kiss Band use mixed codes. The Kiss Band song used in this study is entitled Jauh Panggang Dari Api. The code mix types used in the song Jauh Panggang Dari Api are insertion and alternation. Factors that affect the mixing of codes that occur in the lyrics of the song Jauh Panggaang Dari Api include language dominance, language attitudes and the mixing of words and phrases in the lyrics of Kiss Band.